Performing Magic in the Pre-Modern North Practice and Transgressions - Hemphill, Jennifer; Richardson-Read, Ségdae; Wang, Solveig Marie (Palgrave Historical Studies in Witchcraft and Magic, 2024)
XVII, 294 p. 23 illus.